PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA LUBUKLINGGAU - Suwarno Suwarno; Thoto Massat (LPPM UNIVERSITAS BINA INSAN, 2017)
The study entitled Effect of leadership and organizational culture on the performance of employees in the industrial and trade offices of Lubuklinggau City. This study aims to determine the effect of leadership and organizational culture on employee performance. The sample in this study is 65 employees. Data was collected through questionnaires answered by respondents and then analyzed by multiple regression analysis techniques, using a computer program